Antibacterial Activity of Manganese Dioxide Nanosheets by ROS-Mediated Pathways and Destroying Membrane Integrity - Ting Du; Siya Chen; Jinyu Zhang; Tingting Li; Ping Li; Jifeng Liu; Xinjun Du; Shuo Wang (Nanomaterials, 2020)
Manganese dioxide (MnO2) nanosheets have shown exciting potential in nanomedicine because of their ultrathin thickness, large surface area, high near-infrared (NIR) absorbance and good biocompatibility. However, the effect of MnO2 nanosheets on bacteria is still unclear. In this study, MnO2 nanosheets were shown for the first time to possess highly efficient antibacterial activity by using Salmonella as a model pathogen. The growth curve and surface plate assay uncovered that 125 μg/mL MnO2 nanosheets could kill 99.2% of Salmonella, which was further verified by fluorescence-based live/dead staining measurement. Mechanism analysis indicated that MnO2 nanosheet treatment could dramatically induce reactive oxygen species production, increase ATPase activity and cause the leakage of electrolytes and protein contents, leading to bacterial death. These results uncover the previously undefined role of MnO2 nanosheets and provide novel strategies for developing antimicrobial agents.